Effectiveness of an Awareness Program for Parents on The Risks Associated with Overuse of Smartphones by Children - Jyothi, S.; Dhanya, N. (Journal of Neonatal Surgery, 2025)
The study, titled “Effectiveness of an Awareness Program for Parents on the Risks Associated with Overuse of Smartphones by Children” evaluates the effectiveness of a parental awareness program on the risks of overusing smartphones by children. It draws on data from pre- and post-awareness assessments and focuses on the outcomes of an online safety handbook distributed to parents. The data was gathered from 480 parents using purposive sampling. The awareness program was conducted in two phases, in phase one an awareness program was conducted, and in phase two, a handbook on online safety was distributed. A self-prepared questionnaire is used to gather information from parents. The questionnaire contains various factors to evaluate the effectiveness of the awareness program and handbook developed. Statistical analysis through an ANOVA test reveals a significant improvement in parents' awareness, leading to better protective measures for children's smartphone use. The study underscores the need for an awareness program for parents on the risks associated with the overuse of smartphones by children